Altering scapular position reduces isometric shoulder strength. Issue 4 (10th July 2013) - Matthews, Paul A.; Scott, Martin
ABSTRACT: Background: Strength assessment is an integral part of many clinical tests and some outcome measures. However, shoulder strength may not only be influenced by pathology or treatment effect, but also by scapular position. The present study aimed to examine the influence of scapular positioning on shoulder strength. Methods: Sixteen normal volunteers (seven males and nine females; mean age 35 years) conducted maximal isometric elevation strength tests in scapular positions of self‐selected neutral (SN), maximal protraction (SP), maximal retraction (SR) and posterior tilt (ST), with all of these being assessed in the scapular plane. A prospective, repeated measure, balanced protocol was employed. Results: Resultant strengths were SN = 6.5 kg, SP = 5.0 kg, SR = 5.3 kg and ST = 5.0 kg. Analysis of variance was significant ( p = 0.002) with post‐hoc analysis revealing SN as being significantly stronger than SP ( p = 0.002), SR ( p = 0.004) and ST ( p = 0.001). There were no significant differences between SP, SR and ST. Test–retest analysis yielded intraclass correlation coefficients exceeding 0.85. Conclusions: Altering scapula position may affect shoulder strength in asymptomatic individuals. This has implications for the validity and reliability of shoulder tests and outcome measures that are reliant upon shoulder strength, at the same time as supporting the premise that the application of scapula correction exercises should be based upon individual assessment rather than general prescription.